KUALITAS ANGKATAN KERJA DI KECAMATAN BUKIT SUNDI - yulia, yananda yulia; Suasti, Yurni (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
This research aims to determine the quality of the workforce in terms of the education level of the population aged 18-56 years in Bukit Sundi District in 2022. This type of research is quantitative secondary data analysis. The results of this research found that of the five nagari in Bukit Sundi sub-district, seen from the government service center, the nagari with the highest quality should be Nagari Muaro Paneh, next in terms of proximity to main road access, the most high quality is Nagari Muaro Paneh, but in reality the nagari is very quality is Nagari Parambahan. This means that in Bukit Sundi District, close access to service centers does not apply to determining the quality of the workforce. Theoretically, the theory put forward by Hirschman's theoretical concept explained by Sjafrizal (2008) for Bukit Sundi District does not seem to apply to the quality of the workforce, the proof is that quality nagari are parambahan nagari which are far from the service center in Bukit Sundi District